Controls on the sources and cycling of dissolved inorganic carbon in the Changjiang and Huanghe River estuaries, China: 14C and 13C studies. (5th May 2016) - Wang, Xuchen; Luo, Chunle; Ge, Tiantian; Xu, Caili; Xue, Yuejun
Abstract: The Changjiang (Yangtze River) and Huanghe (Yellow River) are the two largest rivers in China, and they transport large amounts of terrestrial carbon to the coastal waters of the East China Sea and the Bohai Sea. The sources and cycling of riverine carbon in these two large river estuaries, however, have not been well studied. In this article, we present the results of dual isotope (Δ 14 C and δ 13 C) measurements of dissolved inorganic carbon (DIC) collected in the low reaches of the Changjiang and Huanghe and their estuaries during two cruises in 2014. Our results indicate that both the Changjiang and Huanghe carry very high concentrations of DIC ranging from 1384 μ mol kg −1 to 1732 μ mol kg −1 and 2711 μ mol kg −1 to 4120 μ mol kg −1, respectively, and DIC levels varied with flow rates during high and low discharge periods. The cycling of DIC exhibited conservative behavior in both the Changjiang and Huanghe estuaries, suggesting DIC levels were controlled mainly by physical mixing processes. Δ 14 C‐DIC values indicate that the Changjiang and Huanghe transport aged DIC (1060–1380 yr old). Both Δ 14 C‐DIC and δ 13 C‐DIC values also showed conservative mixing in the two estuaries. Using a dual carbon isotopic model, we calculated that atmospheric CO2 consumed mainly by silicate weathering was a major source, contributing 65.2 ± 9.0% and 73.4 ± 3.0% of DIC in the Changjiang and Huanghe, and 96.9–97.7% (by air‐sea exchange) of DIC in the coastal waters of the East China Sea (ECS) and Bohai Sea, respectively. Our results indicate that carbonate dissolution was an important (12.3–17.4%) but not major process controlling the high DIC levels in both rivers, as suggested previously. Compared with the large Amazon River, respiration of riverine organic matter (OM) played a less important role, contributing only 15.4–17.2% of DIC in the two Asian rivers. Flux calculations indicate that the Changjiang and Huanghe discharged 1.46 × 10 13 g and 6.28 × 10 11 g DIC into the ECS and Bohai Sea in 2014, which were 9 and 17 times higher than the DOC fluxes in the two rivers. These large fluxes of riverine DIC, especially of aged DIC, could have significant impacts on primary production and carbon cycling in the ECS and Bohai Sea.